Reviewing reliance on overseas-trained doctors in rural Australia and planning for self-sufficiency: applying 10 years' MABEL evidence - Belinda O'Sullivan; Deborah J. Russell; Matthew R. McGrail; Anthony Scott (BMC, 2019)
Abstract Background The capacity for high-income countries to supply enough locally trained doctors to minimise their reliance on overseas-trained doctors (OTDs) is important for equitable global workforce distribution. However, the ability to achieve self-sufficiency of individual countries is poorly evaluated. This review draws on a decade of research evidence and applies additional stratified analyses from a unique longitudinal medical workforce research program (the Medicine in Australia: Balancing Employment and Life survey (MABEL)) to explore Australia's rural medical workforce self-sufficiency and inform rural workforce planning. Australia is a country with a strong medical education system and extensive rural workforce policies, including a requirement that newly arrived OTDs work up to 10 years in underserved, mostly rural, communities to access reimbursement for clinical services through Australia's universal health insurance scheme, called Medicare. Findings Despite increases in the number of Australian-trained doctors, more than doubling since the late 1990s, recent locally trained graduates are less likely to work either as general practitioners (GPs) or in rural communities compared to local graduates of the 1970s-1980s. The proportion of OTDs among rural GPs and other medical specialists increases for each cohort of doctors entering the medical workforce since the 1970, peaking for entrants in 2005-2009. Rural self-sufficiency will be enhanced with policies of selecting rural-origin students, increasing the balance of generalist doctors, enhancing opportunities for remaining in rural areas for training, ensuring sustainable rural working conditions and using innovative service models. However, these policies need to be strongly integrated across the long medical workforce training pathway for successful rural workforce supply and distribution outcomes by locally trained doctors. Meanwhile, OTDs substantially continue to underpin Australia's rural medical service capacity. The training pathways and social support for OTDs in rural areas is critical given their ongoing contribution to Australia's rural medical workforce. Conclusion It is essential for Australia to monitor its ongoing reliance on OTDs in rural areas and be considerate of the potential impact on global workforce distribution.